Impact analysis of zero-sequence current rounding deviation on time-domain distance protection and its improved algorithm - Mingyu Shao; Jiawei He; Bin Li; Bohao Zhou; Yan Li; Zhongrun Xie; Runbin Cao (International Journal of Electrical Power & Energy Systems)
The time-domain distance protection performs well under the influence of renewable energy generation characteristics, such as frequency offset and phase controlled character, thus having outstanding application prospects in systems with renewable power generation accessed. But, it is discovered that, the fast time-domain distance protection algorithm based on weighted accumulation might mal-operate during system normal operation. The essential reason of this issue is rounding deviation of the zero-sequence current in the protection device. Therefore, this study analyses the effect of rounding deviation in zero-sequence current on the fast time-domain distance protection. And the improved time-domain distance protection algorithm, based on the random correction of zero-sequence current, is proposed. The corresponding protection prototype is developed based on the proposed algorithm. By simulation and hardware-in-loop experiments, it is fully demonstrated that the proposed algorithm effectively mitigates the influence of rounding deviation. Furthermore, the accuracy of distance calculation during faults is not adversely affected.